2021
DOI: 10.21037/apm-21-1671
|View full text |Cite
|
Sign up to set email alerts
|

Association between plasma homocysteine levels and pancreatic islet beta-cell function in the patients with type 2 diabetes mellitus: a cross-sectional study from China

Abstract: Background: This study sought to investigate the association between plasma homocysteine (HCY) levels and pancreatic islet beta-cell function in type 2 diabetes mellitus (T2DM) patients.Methods: 430 hospitalized T2DM patients were enrolled in this cross-sectional study from December 2013 to December 2016. All participants were requested to complete a detailed questionnaire and undergo anthropometric measurements. Blood samples were collected from all participants. A 75-g oral glucose tolerance test (OGTT) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In vitro, homocysteine has been shown to inhibit glucose-induced insulin secretion by β-cells in a dose-dependent manner at moderate (5.6 mM, p < 0.001) and stimulatory (16.7 mM, p < 0.001) glucose concentrations [ 138 , 139 ]. Serum homocysteine was inversely associated with several parameters of pancreatic islet β-cell function, in T2DM patients but a similar effect in GDM has not yet been characterised [ 140 ]. Further research is needed to clarify the relationship between elevated homocysteine and β-cell function in GDM pathogenesis.…”
Section: Association Between One-carbon Metabolism Players and Gdmmentioning
confidence: 99%
“…In vitro, homocysteine has been shown to inhibit glucose-induced insulin secretion by β-cells in a dose-dependent manner at moderate (5.6 mM, p < 0.001) and stimulatory (16.7 mM, p < 0.001) glucose concentrations [ 138 , 139 ]. Serum homocysteine was inversely associated with several parameters of pancreatic islet β-cell function, in T2DM patients but a similar effect in GDM has not yet been characterised [ 140 ]. Further research is needed to clarify the relationship between elevated homocysteine and β-cell function in GDM pathogenesis.…”
Section: Association Between One-carbon Metabolism Players and Gdmmentioning
confidence: 99%
“…of Dl-methionine in drinking water or in diet caused HHcy as recorded by [36,37,38]. Disturbance glycemic indices could indicate susceptibility to diabetes duo to HHcy which was going in line with [39,40]. HHcy could be induced in diabetic patient with elevation in glucose , lipid profile with decrease in HDL-c and insulin [41].Several observational studies have discovered HHcy as a risk factor for T2DM and related complications [42,43,44].As for the underlying mechanisms, it can be speculated that HHcy might cause oxidative stress, and the increased reactive oxygen species act as functional signaling molecules to activate various stress-sensitive signaling pathways, eventually lead to insulin resistance causing hyperglycemia.…”
Section: Discussionmentioning
confidence: 76%
“…Studies indicated that the repair of islet function plays a regulatory role in HCY metabolism and improves oxidative stress in patients, thereby improving the long-term prognosis of patients [ 19 ]. It showed that after two weeks of treatment, HCY level was significantly lower in the experimental group, indicating that islet function was gradually repairing in patients.…”
Section: Discussionmentioning
confidence: 99%